Effects of Aberrations on Point Spread Function of Three Zone Aberrated Optical Imaging System with Variable Apodization - Salkapuram, Vidya Rani; Padamuttum, Anitha; Nampally, Sabitha; Dasari, Karuna Sagar (Photonics Letters of Poland, 2023)
Presence of optical aberrations degrades the performance of the optical system. These effects can be reduced by inserting proper amplitude filters. In the current study, suitable amplitude-apodization pupils have been used for tailoring the point spread function (PSF), in order to attain full-width at half-maximum (FWHM) and suppressed side lobes. Intensity profiles for the unapodized and variable apodized cases have been considered. By comparing and analyzing the various PSFs, the effects induced by monochromatic aberrations such as defocusing effect, and the primary spherical aberration have been controlled for various degrees of apodization parameter β. The proposed apodizer is very effective in increasing the resolution of the optical systems. Full Text: PDF References A.N.K. Reddy, D. Karuna Sagar, Pramana, "Half-width at half-maximum, full-width at half-maximum analysis for resolution of asymmetrically apodized optical systems with slit apertures", J. Phys. 84, 117 (2015). CrossRef A.N.K Reddy, D. Karuna Sagar, "Spherical Aberration of Point Spread Function with Asymmetric Pupil Mask", Adv. Opt. Technol. 2016, 1608342 (2016). CrossRef W. Yang, A.B. Kotinski, "One-sided Achromatic Phase Apodization for Imaging of Extrasolar Planets", The Astrophys. J. 605, 892 (2004). CrossRef M. Kowalczyk, C.J. Zapata-Rodriguez, M. Martinez-Corral, "Asymmetric apodization in confocal scanning systems", Appl. Opt. 37, 8206 (1998). CrossRef S.C. Biswas, A. Boivin, "Influence of Spherical Aberration on the Performance of Optimum Apodizers", Opt. Acta 23, 569 (1976). CrossRef A.N.K. Reddy, S.N. Khonina, "Analysis of electronic parameters and frequency-dependent properties of Au/NiO/n-GaN heterojunctions", Appl. Phys. B. 124, 1 (2018). CrossRef D. Karuna Sagar, G. Bikshamaiah, S.L. Goud, "Defect of focus in two-line resolution with Hanning amplitude filters", J. Mod.Opt. 53, 2011 (2006). CrossRef M. Ruphy, O.M. Ramahi, "Spherical aberration in electrically thin flat lenses", J. Opt. Soc. Am. A 33, 1531(2016). CrossRef A.N.K. Reddy, M. Hashemi, D.K. Sagar, "Effects of aberrations on the point spread function and the two-point resolution with versatile apodization pupils", Pramana J. Phy. 94, P. 1 (2020). CrossRef A.N.K. Reddy, D.K. Sagar, "Two-point resolution of asymmetrically apodized optical systems", Optica Pura y Aplicada 46, 215 (2013). CrossRef